Combined multidisciplinary in/outpatient rehabilitation delays definite nursing home admission in advanced Parkinson’s disease patients - Steendam-Oldekamp, Elien; Weerkamp, Nico; Vonk, Judith M.; Bloem, Bastiaan R.; van Laar, Teus (Frontiers in Neurology, 2023)
Introduction Advanced Parkinson’s disease (aPD) patients have a high risk on definite nursing home admission. We analyzed the effectiveness of an in-and outpatient multidisciplinary rehabilitation, focusing on activities of daily living (ADL) and delaying definite nursing home admission. Methods This study included 24 aPD patients, who received a 6-week inpatient multidisciplinary rehabilitation program, including optimization of pharmacotherapy, which was followed by an individualized outpatient support program during 2 years (intervention group). A non-randomized matched control group (n = 19), received care as usual. Primary endpoints consisted of the Amsterdam Linear Disability Scale (ALDS) and percentage of patients being able to live independently at home after 2 years. Secondary endpoints included changes in medication (LEDD), motor performance (SCOPA-SPES), cognition (SCOPA-COG), hallucinations (NPI) and depression (BDI). Results Overall, 83% of patients were able to return home after the 6-week inpatient intervention, and 65% still lived at home at 2 years follow-up. Median ALDS scores after 2 years in the intervention group were significantly better, compared to the control group (p = 0.002). All secondary endpoints had improved significantly vs. baseline directly after the 6-week inpatient rehabilitation, which had disappeared at 2 years follow-up, with the exception of the daily dose of medication, which was significantly higher in the intervention group. Conclusion This 2-year follow-up study showed that a combined multidisciplinary in/outpatient rehabilitation program for aPD patients, was able to stabilize ADL functions, and finally delayed definite nursing home admissions in 65% of treated patients. Trial registration filenumber M10.091051; ABR code NL32699.042.10.